The Relation of Contentment and Mental Health in al-Hikam - Windariyah, Devi Suci (Buletin Al-Turas, 2025)
PurposeThis study aimed to explore the relationship of contentment values with mental health theory in enhancing emotional stability and reducing reliance on materialistic ambitions that were often the cause of psychological instability. MethodUsing a qualitative descriptive approach, this study objectively analyzes the book al-H{ikam by Ibn Atha’ilah, using a qualitative descriptive approach. Primary data was obtained from the text of al-H{ikam, while secondary data was obtained from literature related to mental health and spirituality. Results/findingsResearch findings suggest that contentment helps individuals reduce psychological distress by promoting mental resilience through the mechanisms of self-acceptance and gratitude. The practice also provides sustained inner peace, even under stressful circumstances. ConclusionThis research concludes that contentment has the potential to be integrated into modern mental health approaches, both in a spiritual and multicultural context. By translating the values of contentment into the language of modern psychology, the concept becomes accessible to a wider audience. These findings pave the way for the development of innovative and relevant spirituality-based interventions to address global mental health challenges.